Validation of a focused echocardiographic training program in first opinion practice. (11th October 2022) - Dickson, David; Harris, Joanne; Chang, Chia‐Hsuan; Patteson, Mark; Hezzell, Melanie J.
Abstract: Background: The EPIC study defines criteria, including echocardiographic assessments of left atrial to aortic ratio (LA: Ao) and left ventricular internal diameter in diastole normalized for body weight (LVIDdN), for dogs with preclinical myxomatous mitral valve disease (MMVD) likely to benefit from pimobendan therapy. Access to echocardiography by a cardiologist is not universally available. Hypothesis/Objectives: Completion of a focused echocardiographic training program would result in accurate identification of dogs fulfilling the EPIC criteria by primary care veterinarians (PC). Participants: Six PCs with no previous echocardiographic experience. Methods: Prospective diagnostic test accuracy study. After training, each PC evaluated ≤10 dogs that they believed to have preclinical MMVD. The evaluation was repeated by 1 of 3 cardiology diplomates, blinded to the PC's findings. Agreement between clinical assessments and echocardiographic measurements was assessed. Results: Fifty‐seven dogs were evaluated by PCs; 1 dog was withdrawn because of congestive heart failure. The median time between PC and cardiologist evaluation was 0 days (range, 0‐8). One incorrect diagnosis of MMVD was made by a PC (this dog had dilated cardiomyopathy [DCM]); preclinical MMVD was confirmed by the cardiologist in 55 dogs. No difference in LA: Ao ( P  = .96; CV = 6.9%) was detected between PCs and cardiologists. LVIDdN (1.69 cm/kg 0.294 (1.26‐2.21) vs 1.73 cm/kg 0.294 (1.32‐2.73); P  = .001; CV = 6.5%), was significantly lower when measured by PCs vs cardiologists. PCs and cardiologists agreed regarding assessment of EPIC criteria in 49/56 dogs (Alpha = .761, 95% confidence interval 0.697‐0.922). Conclusions and Clinical Importance: The program effectively trained PCs to accurately assess EPIC criteria in dogs with preclinical MMVD.